Pemanfaatan E-Commerce Sebagai Alat Untuk Mengembangkan Minat Berwirausaha Pada Siswa Smk Dimasa Pandemi Covid 19 - Novitasari, Desi; Sari, Diana; Wijanarko, Hanif; Ruhiyat, Ilyas; Junita, Leni Marlina (Universitas Pamulang, 2021)
Title in English. The Student Service to the Community (PMKM) is a form of the responsibility of a student after completing a study assignment on college to transfer, transform, and apply knowledge from within the college to the community. To realize this, Pamulang University students took the initiative to carry out PMKM activities with the theme Utilizing E-Commerce as a Tool to Develop Entrepreneurial Interest in Vocational Schools. The purpose of this PMKM is to motivate students of SMK Harapan Raya Jakarta to foster their interest in entrepreneurship through e-commerce during the Covid 19 pandemic. Activities are carried out using lecture, discussion, and question and answer methods. After participating in this activity, participants with different backgrounds are expected to be able to set up businesses to help the government in creating jobs, and move the wheels of the Indonesian economy which had grown negatively due to the Covid 19 pandemic. Keywords: PMKM, Entrepreneurship, E Commerce, Students, Pandemic.